2014
DOI: 10.1186/1471-2164-15-791
|View full text |Cite
|
Sign up to set email alerts
|

Different nucleosomal architectures at early and late replicating origins in Saccharomyces cerevisiae

Abstract: BackgroundEukaryotic genomes are replicated during S phase according to a temporal program. Several determinants control the timing of origin firing, including the chromatin environment and epigenetic modifications. However, how chromatin structure influences the timing of the activation of specific origins is still poorly understood.ResultsBy performing high-resolution analysis of genome-wide nucleosome positioning we have identified different chromatin architectures at early and late replication origins. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 56 publications
4
41
2
3
Order By: Relevance
“…Instead of a global role in controlling origin activity, the wildtype level of HU sensitivity of rrm3Δ cells, the less pronounced S phase progression in HU than that of the rad53 Δ mutant, and the importance of Rrm3 for replicating through certain nonhistone-protein-bound regions suggest that Rrm3 may play a role at origins in specific loci, such as those in highly transcribed regions and regions with converging transcription, which are often late-firing [57], rRNA and tRNA coding loci, or highly transcribed metabolic genes, where ORC has been found to be bound to the open reading frames, possibly to coordinate the timing of replication with transcription [58]. Indeed, our analysis so far has revealed that Rrm3 appears to associate only with a subset of replication origins.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of a global role in controlling origin activity, the wildtype level of HU sensitivity of rrm3Δ cells, the less pronounced S phase progression in HU than that of the rad53 Δ mutant, and the importance of Rrm3 for replicating through certain nonhistone-protein-bound regions suggest that Rrm3 may play a role at origins in specific loci, such as those in highly transcribed regions and regions with converging transcription, which are often late-firing [57], rRNA and tRNA coding loci, or highly transcribed metabolic genes, where ORC has been found to be bound to the open reading frames, possibly to coordinate the timing of replication with transcription [58]. Indeed, our analysis so far has revealed that Rrm3 appears to associate only with a subset of replication origins.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of histone occupancy near early and late replication origins was performed similarly. Replication origin coordinates were from a published data set (30). …”
Section: Methodsmentioning
confidence: 99%
“…2C). Early origins tend to have both larger NFRs and higher rates of nucleosome exchange [30,34], both of which could lead to increased MCM loading. Finally, a number of trans-acting factors, such as Rif1, Rpd3, and Fkh1, have been shown to regulate origin timing [35][36][37][38] (Fig.…”
Section: How Is Multiple MCM Loading Regulated?mentioning
confidence: 99%